Serum Procalcitonin and Peripheral Venous Lactate for Predicting Dengue Shock and/or Organ Failure: A Prospective Observational Study - Vipa Thanachartwet (2018)
© 2016 Thanachartwet et al. Background: Currently, there are no biomarkers that can predict the incidence of dengue shock and/or organ failure, although the early identification of risk factors is important in determining appropriate management to reduce mortality. Therefore, we sought to determine the factors associated with dengue shock and/or organ failure and to evaluate the prognostic value of serum procalcitonin (PCT) and peripheral venous lactate (PVL) levels as biomarkers of dengue shock and/or organ failure. Methodology/Principal Findings: A prospective observational study was conducted among adults hospitalized for confirmed viral dengue infection at the Hospital for Tropical Diseases in Bangkok, Thailand between October 2013 and July 2015. Data, including baseline characteristics, clinical parameters, laboratory findings, serum PCT and PVL levels, management, and outcomes, were recorded on pre-defined case report forms. Of 160 patients with dengue, 128 (80.0%) patients had dengue without shock or organ failure, whereas 32 (20.0%) patients developed dengue with shock and/or organ failure. Using a stepwise multivariate logistic regression analysis, PCT ≥0.7 ng/mL (odds ratio [OR]: 4.80; 95% confidence interval [CI]: 1.60–14.45; p = 0.005) and PVL ≥2.5 mmol/L (OR: 27.99, 95% CI: 8.47–92.53; p <0.001) were independently associated with dengue shock and/or organ failure. A combination of PCT ≥0.7 ng/mL and PVL ≥2.5 mmol/L provided good prognostic value for predicting dengue shock and/or organ failure, with an area under the receiver operating characteristics curve of 0.83 (95% CI: 0.74–0.92), a sensitivity of 81.2% (95% CI: 63.6–92.8%), and a specificity of 84.4% (95% CI: 76.9–90.2%). Dengue shock patients with non-clearance of PCT and PVL expired during hospitalization. Conclusions/Significance: PCT ≥0.7 ng/mL and PVL ≥2.5 mmol/L were independently associated with dengue shock and/or organ failure. The combination of PCT and PVL levels could be used as prognostic biomarkers for the prediction of dengue shock and/or organ failure.